Sleep and happiness: socio-economic, population and cultural correlates of sleep duration and subjective well-being in 52 countries - Lajunen, Timo; Gaygısız, Esma; Wang, Wei (Frontiers in Sleep, 2023)
Getting enough sleep is one of the essential lifestyle factors influencing health and well-being. However, there are considerable differences between countries in how much people sleep on average. The present study investigated how socio-economic factors, population variables, and cultural value dimensions are related to sleep duration in a sample of 52 countries. Hence, the study design was ecological, i.e., the aggregate values for each country were obtained, and their correlations to national average sleep duration were analysed. The sleep duration estimates were based on Sleep Cycle Application (Sleep Cycle AB, Gothenburg, Sweden) data. The socio-economic variables included the economic health of a country (GDP per capita), how well a country is governed (governance quality measured with WGI), and the economic inequality (the gap between rich and poor measured with the Gini index) within a nation. The population variables included the urbanisation rate (proportion of people living in urbanised areas), life expectancy at birth, mean years of schooling among the population aged 25 years and older, median age of the population, and the prevalence of obesity (% of adults with BMI≥30). The cultural value dimensions were measured with Hofstede's cultural value dimensions (power distance, individualism, masculinity, uncertainty avoidance, long-term orientation, and indulgence). The data were analysed by using zero-order correlations, partial correlations, and canonical correlation analyses. Results showed a relatively strong intercorrelation between the national average of sleep duration and national happiness, i.e., subjective well-being. Among the socio-economic variables, WGI had the strongest relationship to sleep, whereas among population variables, schooling and obesity had the strongest correlations with sleep. Zero-order correlations between sleep and power distance and individualism were statistically significant, whereas in the partial correlations, individualism and masculinity appeared as important factors. Canonical correlation analysis showed strong correlations between the well-being variables (sleep and happiness) and the socio-economic variables, well-being variables and population variables, and cultural values and well-being variables. The present study is an opening for a new line of research in which sleep is seen as an essential part of societal life and collective well-being.